PENDEKATAN SOCIO-LEGAL TERHADAP PERLINDUNGAN HAK-HAK ANAK KORBAN KEKERASAN SEKSUAL - Gemilang, Muhammad Surya; Idris, Irma (Legislatif, 2024)
Sexual violence against children is a social problem that requires attention and active involvement from the wider community. The urgency of this problem arises based on a report from the Ministry of Women's Empowerment and Child Protection of the Republic of Indonesia, which recorded 3,015 cases of violence against children between January 1, 2022 and March 17, 2023. This research aims to provide legal protection that should be given to child victims of sexual violence and identify various obstacles in efforts to fulfill their rights. The research was conducted using a socio-legal approach involving interviews and literature review as data collection techniques. The results showed that legal protection includes reproductive health education, social rehabilitation, victim recovery, as well as rights advocacy and legal protection. This also arises because there are obstacles such as the uncertainty of victim handling regulations, lack of competence of legal personnel, limited facilities, and negative stigma in the community that hinder the fulfillment of the rights of child victims of sexual violence.